Perspektywy ujęcia odpowiedzialności - Niećko-Bukowska, Bożena (Investigationes Linguisticae, 2008)
The purpose of this article is to analyze the possible perspectives relating to responsibility. The purpose of the initial section is to describe the development of the notion of responsibility. The most important issues are the problem of biosferic responsibility and the phenomenons of responsibility including the call to account, arraign or to bear the responsibility.